2002
DOI: 10.1038/ng1058
|View full text |Cite
|
Sign up to set email alerts
|

Positional identification of Ncf1 as a gene that regulates arthritis severity in rats

Abstract: The identification of genes underlying quantitative-trait loci (QTL) for complex diseases, such as rheumatoid arthritis, is a challenging and difficult task for the human genome project. Through positional cloning of the Pia4 QTL in rats, we found that a naturally occurring polymorphism of Ncf1 (encoding neutrophil cytosolic factor 1, a component of the NADPH oxidase complex) regulates arthritis severity. The disease-related allele of Ncf1 has reduced oxidative burst response and promotes activation of arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
360
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 341 publications
(371 citation statements)
references
References 50 publications
9
360
1
1
Order By: Relevance
“…This locus also showed a strong effect on disease, since the E3 allele of this locus conferred 90% protection against arthritis severity in PIA (Figure 3). Recently, the Cia12/Pia4 QTL was found to confer structural polymorphism in the Ncf1 gene (35). The effect of this genetic variation resulted in differential production of free radicals by the NADPH oxidase complex (36).…”
Section: Discussionmentioning
confidence: 99%
“…This locus also showed a strong effect on disease, since the E3 allele of this locus conferred 90% protection against arthritis severity in PIA (Figure 3). Recently, the Cia12/Pia4 QTL was found to confer structural polymorphism in the Ncf1 gene (35). The effect of this genetic variation resulted in differential production of free radicals by the NADPH oxidase complex (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of oxygen radicals promotes inflammation by breaking T-cell tolerance to CII, 29 and the inflammation is probably mediated via CD68 ϩ cells during the process of antigen presentation, 56 which in turn could affect APC-T-cell interactions and the resulting T-cell priming and activation. 27,57 We also reported that Ncf1-associated, reduced oxidative environment promotes IL33 ϩ -dependent, T cell-mediated, adjuvant-free arthritis in mice. 58 In the present study, we found that PNiPAAm-CII immunization led to significantly enhanced incidence and severity of arthritis in the Ncf1 mutated mice compared with wild-type littermate controls.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, our recent studies demonstrated Ncf1 (coding p47 phox subunit of the NA-DPH oxidase complex, which is a multicomponent electron carrier that is responsible for the reduction of oxygen, resulting in the production of ROS) polymorphism as one of the major genetic factors that control arthritis severity and chronicity, regulating autoimmune reactions and impaired tolerance to CII. [27][28][29] In addition, we have also observed a high frequency of arthritis after CII immunization without any adjuvant in a transgenic mice expressing a CII-specific TCR V␤12 chain that recognizes the immunodominant glycosylated CII260Ϫ270 peptide that is dependent on eosinophilic inflammation. 30 Hence, in the present study, we tested various mouse strains using PNiPAAm-CII immunization to find genetic restriction of arthritis development in the absence of a classical adjuvant.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…15 Based on their thought role in protecting cells from oxidative stress, several GSTs have been suggested as candidate genes for cancer, 16 arthritis, 17 hypertension 18 and asthma. 19 However, the lower levels of Gstm1 and Gstm2 in the congenic strain might play a protective role during the induction phase of CIA, since reduced oxidative burst response has been shown to promote activation of arthritogenic T cells, both in pristane-induced arthritis (PIA) in rats 20 and in CIA in mice. 21 Tspan-2, which is one of the candidates for Cia21, 5 is also a possible candidate for the insulin-dependent diabetes loci 10, Idd10, mapped to the same region.…”
Section: Discussionmentioning
confidence: 99%